Educational outcomes are predictive of mental health diagnoses in adolescence: IJPDS (2017) Issue 1, Vol 1:198, Proceedings of the IPDLN Conference (August 2016) - Wong, Janice; Fletcher, Janet; Glauert, Rebecca; O'Donnell, Melissa; Bayliss, Donna (International Journal of Population Data Science, 2017)
ABSTRACT Objectives Associations between poor reading outcomes and attention/behavioural difficulties have been documented in the literature (e.g., Spira & Fischel, 2005), however the research regarding the relationship between reading achievement and internalising mental health disorders (e.g., mood disorders, anxiety) is scarce. As children experience a large proportion of their development in the school context, it is essential to understand the nature of this relationship, as it may inform a population based approach to reducing the risk of mental health disorders. Approach This study was a retrospective cohort study, and utilised population level administrative data. Participants included all children born in Western Australia between 1992 and 1996. Individuals were followed until 2011 for their mental health outcomes. Using Cox regressions, variables reflecting child, family, and community factors, as well as factors from the school context were used to predict the risk of any mental health disorder, and also more specifically, an internalising or externalising mental health disorder. Results After controlling for a number of demographic risk factors, poor reading achievement in Year 3 and Year 7 appeared to be associated with poor mental health when all mental health diagnostic codes were considered as a single entity. However, when mental health was grouped into internalising or externalising mental health disorders, findings showed that reading achievement in the top 20% of the cohort was associated with an increased risk of an internalising disorder, whilst reading achievement in the bottom 20% of the cohort was associated with an increased risk of an externalising disorder. Conclusion This study found that reading achievement is associated with mental health, but the nature of this relationship appears to be dependent on the type of mental health disorders that are considered. A more complex relationship between reading achievement and poor mental health was revealed when the mental health diagnoses were grouped into internalising and externalising disorders. Whilst further research is required to understand the factors that may mediate these relationships (e.g., perfectionism for high achieving students), the provision of support to both ends of the achievement spectrum may play a role in reducing the risk of adolescent mental health disorders.